Polymer dispersed liquid crystal film
By designing liquid crystal droplet components and conductive substrate structures in different regions in the polymer dispersed liquid crystal film, the transparent state and the scattered state are switched in a predetermined region, and the light resistance of the film is improved through the ultraviolet blocking layer, solving the problem of insufficient area switching and light resistance in the prior art.
Patent Information
- Application Number
- CN202380059683.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-11
AI Technical Summary
The conventional polymer dispersed liquid crystal film cannot switch between transparent state and scattered state in a predetermined area, and light resistance is insufficient.
The structure including a first conductive substrate, a polymer dispersible liquid crystal layer and a second conductive substrate is adopted. The polymer dispersible liquid crystal layer has a first region and a second region with different haze changes in plan view. The liquid crystal droplets in the first region contain liquid crystal polymers, and the liquid crystal droplets in the second region contain polymerizable and non-polymerizable liquid crystal compounds, and an ultraviolet blocking layer is added to the first conductive substrate.
The function of switching the transparent state and the scattered state in a predetermined area is realized, and the light resistance of the film is improved by the ultraviolet blocking layer.
Smart Images

Figure CN119604809A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer dispersed liquid crystal film. Background Art
[0002] In recent years, light-control films that display different appearances depending on the voltage applied have been used in various applications such as advertisements, display bodies such as billboards, and smartphones.
[0003] The PDLC film having a polymer dispersed liquid crystal (PDLC; hereinafter sometimes referred to as "PDLC") layer between a pair of transparent electrode layers is a type of dimming film, which can switch between a state in which light is scattered (scattering state) and a state in which light is transmitted (non-scattering state or transparent state) by switching between a voltage applied state and a voltage not applied state. Specifically, the PDLC layer includes a polymer matrix and droplets of liquid crystal compounds dispersed in the polymer matrix (liquid crystal droplets). Due to the difference in refractive index between the liquid crystal compounds in the liquid crystal droplets and the polymer matrix, the liquid crystal droplets become scattering particles and light scattering occurs.
[0004] The PDLC film generally has a turbid appearance in a scattering state, and thus can have two appearances, turbid (scattering state) and transparent (non-scattering state). However, in consideration of design, a light-adjusting film that can have other appearances is desired.
[0005] Regarding the above expectation, Patent Document 1 proposes the following dimming film as a dimming film that can adjust the overall incident light amount. The dimming film does not use liquid crystal compounds but uses dichroic substances, thereby presenting a transparent appearance in a non-scattering state and a colored appearance in a scattering state.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2002-189123 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In the conventional light-adjusting film, the switching between the transparent state and the scattering state is performed on the entire surface of the film, and it is not possible to perform the switching only in a predetermined area.
[0011] The present invention is made to solve the above-mentioned previous problems, and its main purpose is to provide a polymer dispersed liquid crystal film that can switch between a transparent state and a scattering state only in a predetermined area, and its further purpose is to improve the light resistance in such a polymer dispersed liquid crystal film.
[0012] Means for solving problems
[0013] [1] The polymer dispersed liquid crystal film according to the embodiment of the present invention comprises, in sequence, a first conductive substrate, a polymer dispersed liquid crystal layer and a second conductive substrate, the polymer dispersed liquid crystal layer comprising a polymer matrix and liquid crystal droplets and a photopolymerization initiator dispersed in the polymer matrix, the polymer dispersed liquid crystal layer having, when viewed from above, a first region and a second region having different haze changes after application of a voltage, the haze change in the first region after application of a voltage being smaller than the haze change in the second region after application of a voltage, the liquid crystal droplets in the second region comprising a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound, the liquid crystal droplets in the first region comprising a liquid crystal polymer which is a polymer of the polymerizable liquid crystal compound and the non-polymerizable liquid crystal compound, and the first conductive substrate comprises a UV blocking layer.
[0014] [2] In the polymer dispersed liquid crystal film described in the above [1], the absorbance of the above ultraviolet blocking layer at a wavelength of 350 nm may be 2 or more.
[0015] [3] In the polymer dispersed liquid crystal film described in [1] or [2] above, when the maximum absorption wavelength on the longest wavelength side of the above-mentioned photopolymerization initiator is set to Ann, the absorbance of the above-mentioned ultraviolet blocking layer in the wavelength range of A-30nm~A+50nm can also be greater than 5.
[0016] [4] In the polymer dispersed liquid crystal film described in any one of [1] to [3] above, when the maximum absorption wavelength on the longest wavelength side of the above-mentioned photopolymerization initiator is set to Ann, the absorbance of the above-mentioned ultraviolet blocking layer at a wavelength of A+70nm may also be greater than 1.8.
[0017] [5] In the polymer dispersed liquid crystal film described in any one of [1] to [4] above, the photopolymerization initiator may have a maximum absorption wavelength in the range of 300 nm to 340 nm.
[0018] [6] In the polymer dispersed liquid crystal film described in any one of [1] to [5] above, the second conductive substrate may include an ultraviolet blocking layer or a reflecting layer.
[0019] [7] In the polymer dispersed liquid crystal film described in any one of [1] to [6] above, the weight ratio of the non-polymerizable liquid crystal compound to the polymerizable liquid crystal compound in the second region (non-polymerizable liquid crystal compound: polymerizable liquid crystal compound) may be 99:1 to 70:30.
[0020] [8] In the polymer dispersed liquid crystal film described in any one of [1] to [7] above, the difference between the haze of the first region and the haze of the second region increases due to application of voltage.
[0021] [9] In the polymer dispersed liquid crystal film described in any one of [1] to [7] above, the difference between the haze of the first region and the haze of the second region is reduced by application of voltage.
[0022] Effects of the Invention
[0023] According to an embodiment of the present invention, in the liquid crystal droplets in the first region, the liquid crystal compound is restricted in orientation by the liquid crystal polymer, and as a result, the change in haze caused by the change in the voltage application state is suppressed. On the other hand, in the liquid crystal droplets in the second region, the orientation state of the liquid crystal compound changes according to the voltage application state, which can greatly change the haze. Therefore, by forming the first region and the second region in a desired pattern, a dimming film can be provided, which presents an appearance with a predetermined pattern in either case when the voltage is applied or when the voltage is not applied, and presents a highly uniform appearance in the other case. In addition, at least one of the pair of conductive substrates sandwiching the PDLC layer includes an ultraviolet blocking layer, thereby preventing the generation of liquid crystal polymers in the liquid crystal droplets in the second region due to exposure to sunlight, etc., and reducing the amount of haze change in the second region, and improving light resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 In the figure, (a) is a schematic top view of an example of a PDLC film according to the first embodiment of the present invention; (b) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when no voltage is applied; and (c) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when a voltage is applied.
[0025] Figure 2 This is a schematic cross-sectional view of an example of a first conductive substrate that can be used for the PDLC film according to the embodiment of the present invention.
[0026] Figure 3 In the figure, (a) is a schematic top view of an example of a PDLC film according to a second embodiment of the present invention; (b) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when no voltage is applied; and (c) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when a voltage is applied.
[0027] Figure 4 This is a schematic diagram for explaining an example of the method for producing the PDLC film of the present invention.
[0028] Figure 5This is a schematic diagram for explaining an example of the method for producing the PDLC film of the present invention.
[0029] Figure 6 It is a schematic cross-sectional view of a modified example of the PDLC film according to the embodiment of the present invention.
[0030] Figure 7 It is a schematic cross-sectional view of a modified example of the PDLC film according to the embodiment of the present invention.
[0031] Figure 8 This is a schematic cross-sectional view of an example of a reflective layer that can be used in the PDLC film according to the embodiment of the present invention.
[0032] Fig. 9 This is a graph showing the light resistance evaluation results of the PDLC film of Comparative Example 1.
[0033] Fig.10 The graphs show the light resistance evaluation results of the PDLC films of Examples 1 to 3 and the absorption spectra of the ultraviolet blocking layers used for the PDLC films. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention are described below, but the present invention is not limited to these embodiments. With respect to the accompanying drawings, in order to make the description clearer, there is a case where the width, thickness, shape, etc. of each part are schematically represented compared to the embodiment, but this is only an example and does not limit the interpretation of the present invention. Except for the case where such an understanding is obviously inappropriate from the context, the various embodiments can be appropriately combined. In addition, in this specification, the symbol "~" indicating a numerical range includes the numerical value of its upper limit and lower limit.
[0035] A. Polymer dispersed liquid crystal film
[0036] The polymer dispersed liquid crystal (PDLC) film of the embodiment of the present invention comprises a first conductive substrate, a polymer dispersed liquid crystal layer and a second conductive substrate in sequence, wherein the polymer dispersed liquid crystal layer comprises a polymer matrix and liquid crystal droplets and a photopolymerization initiator dispersed in the polymer matrix. The first conductive substrate comprises an ultraviolet blocking layer. The polymer dispersed liquid crystal layer comprises a first region and a second region having different haze changes after voltage application in a plan view, wherein the haze change after voltage application in the first region is smaller than the haze change after voltage application in the second region. The liquid crystal droplets in the second region comprise a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound. The liquid crystal droplets in the first region comprise a liquid crystal polymer as a polymer of the polymerizable liquid crystal compound, and the non-polymerizable liquid crystal compound.
[0037] A-1. PDLC film of the first embodiment
[0038] Figure 1 (a) is a schematic top view of an example of a PDLC film according to the first embodiment of the present invention, (b) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when no voltage is applied, and (c) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when a voltage is applied. The PDLC film 100a sequentially comprises: a first conductive substrate 10 including an ultraviolet blocking layer 16; a PDLC layer 20 including a polymer matrix 22 and liquid crystal droplets 24 and a photopolymerization initiator 26 dispersed in the polymer matrix 22; and a second conductive substrate 30. The PDLC layer 20 has a first region A and a second region B in which the haze change amount after voltage application is different when viewed from above. The liquid crystal droplets 24 in the second region B include a polymerizable liquid crystal compound 24a and a non-polymerizable liquid crystal compound 24b. The liquid crystal droplets 24 in the first region A include a liquid crystal polymer 24c and a non-polymerizable liquid crystal compound 24b. Typically, the liquid crystal polymer 24c exists in a non-oriented state. The photopolymerization initiator 26 is dispersed in the polymer matrix 22, and at least a part of the photopolymerization initiator 26 is also contained in the liquid crystal droplets 24. In this specification, a compound being in a "non-aligned state" means that the compound is in a state with fixed regularity and is not arranged.
[0039] like Figure 1 As shown in (b), in the PDLC film 100a when no voltage is applied, the non-polymerizable liquid crystal compound 24b and the liquid crystal polymer 24c in the liquid crystal droplet 24 in the first region A are both in a non-oriented state, and the polymerizable liquid crystal compound 24a and the non-polymerizable liquid crystal compound 24b in the liquid crystal droplet 24 in the second region B are both in a non-oriented state, so that scattering of the transmitted light occurs in any region. Therefore, both the first region A and the second region B can be in a scattering state, and as a result, the entire main surface of the PDLC film 100a can be in a scattering state.
[0040] On the other hand, Figure 1 As shown in (c), in the PDLC film 100a when voltage is applied, the polymerizable liquid crystal compound 24a and the non-polymerizable liquid crystal compound 24b in the liquid crystal droplet 24 in the second region B are oriented in a direction perpendicular to the main surface of the first conductive substrate 10 and the second conductive substrate 30, and the scattering of the transmitted light is suppressed, so the haze of this region is reduced. On the other hand, in the first region A, due to the presence of the non-oriented liquid crystal polymer 24c, the orientation of the non-polymerizable liquid crystal compound 24b is hindered and the non-oriented state is maintained, so the scattering of the transmitted light still occurs. Therefore, the change in haze after voltage application in the first region is smaller than that in the second region, and the difference between the haze of the first region and the haze of the second region increases due to the application of voltage.
[0041] As described above, when no voltage is applied, the entire main surface of the PDLC film 100a is in a scattered state and presents a turbid appearance. On the other hand, by applying a voltage, the haze of only the second region is greatly reduced, the first region can present a turbid appearance, and the second region can present a transparent appearance. Therefore, the PDLC film 100a can present different appearances by switching between applying and not applying a voltage.
[0042] The voltage applied to the PDLC film during voltage application is a voltage (operation voltage) that can cause the PDLC film to operate, and may be, for example, 5 V to 200 V, and preferably 10 V to 100 V. In this specification, "haze during voltage application" means haze when an operation voltage is applied to the PDLC film, and may be, for example, haze when a voltage of 5 V or more, 10 V or more, or 20 V or more is applied.
[0043] The haze of the region of the PDLC film corresponding to the first region when no voltage is applied (hereinafter sometimes referred to as "the haze of the first region") is, for example, 50% to 100%, preferably 70% to 100%. The haze of the first region when voltage is applied is, for example, 40% to 100%, preferably 60% to 100%. The change in haze of the first region after voltage application (|haze when voltage is not applied - haze when voltage is applied|) is, for example, 0% to 40%, preferably 0% to 30%.
[0044] The haze of the region corresponding to the second region of the PDLC film when no voltage is applied (hereinafter sometimes referred to as "the haze of the second region") is, for example, 50% to 100%, preferably 70% to 100%. The haze of the second region when voltage is applied is, for example, 1% to 20%, preferably 1% to 10%. The change in haze of the second region after voltage application (|haze when no voltage is applied - haze when voltage is applied|) is, for example, 30% to 99%, preferably 60% to 99%.
[0045] The amount of change in haze of the first region after voltage application is smaller than the amount of change in haze of the second region after voltage application, and the difference is, for example, 10% to 99%, preferably 30% to 99%.
[0046] When no voltage is applied, the total light transmittance of the region of the PDLC film corresponding to the first region (hereinafter sometimes referred to as "the total light transmittance of the first region") is, for example, 50% to 95%, preferably 60% to 90%. When voltage is applied, the total light transmittance of the first region is, for example, 50% to 95%, preferably 60% to 90%. The total light transmittance can be measured in accordance with JIS K 7361.
[0047] When no voltage is applied, the total light transmittance of the region of the PDLC film corresponding to the second region (hereinafter sometimes referred to as "the total light transmittance of the second region") is, for example, 50% to 95%, preferably 60% to 90%. When voltage is applied, the total light transmittance of the second region is, for example, 70% to 95%, preferably 80% to 90%.
[0048] At 30°C and 55% RH, the first conductive substrate was exposed to 120 W / m 2 The haze change Va (|haze when voltage is applied - haze when voltage is not applied|) of the second area after applying voltage (e.g., 50V) 125 hours after (300nm-400nm) irradiation with xenon light and the haze change Vb of the second area before irradiation after applying voltage (e.g., 50V) satisfy the relationship of (Vb-Va) / Vb×100≤5, and preferably satisfy the relationship of (Vb-Va) / Vb×100≤3.
[0049] The thickness of the PDLC film is, for example, 30 μm to 250 μm, and preferably 50 μm to 150 μm.
[0050] A-1-1. First conductive substrate
[0051] The first conductive substrate 10 includes a first transparent substrate 12, a first transparent electrode layer 14 disposed on one side thereof, and an ultraviolet blocking layer 16 disposed on the other side. The first conductive substrate 10 may further include any appropriate functional layer as required. For example, the first conductive substrate 10 may include a hard coating layer on one side or both sides of the ultraviolet blocking layer 16, and may also include a refractive index adjustment layer between the first transparent substrate 12 and the first transparent electrode layer 14. The first conductive substrate is disposed on the side of the PDLC film that is exposed to light containing ultraviolet rays (e.g., sunlight, emitted light from various light sources).
[0052] The surface resistance value of the first transparent electrode layer-side surface of the first conductive substrate is preferably 1 Ω / □ to 1000 Ω / □, more preferably 5 Ω / □ to 300 Ω / □, and further preferably 10 Ω / □ to 200 Ω / □.
[0053] The haze of the first conductive substrate is preferably 20% or less, more preferably 10% or less, and further preferably 0.1% to 10%.
[0054] The total light transmittance of the first conductive substrate is preferably 30% or more, more preferably 60% or more, and even more preferably 80% or more.
[0055] The first transparent substrate 12 can be formed using any appropriate material. Specifically, a polymer substrate such as a film or a plastic substrate can be preferably used. This is because the first transparent substrate 12 has excellent smoothness and wettability to the transparent electrode layer forming composition, and can significantly improve productivity by continuous production using a roller.
[0056] Regarding the material constituting the first transparent substrate, a representative one is a polymer film with a thermoplastic resin as the main component. As thermoplastic resins, for example, polyester resins; cycloolefin resins such as polynorbornene; acrylic resins; polycarbonate resins; cellulose resins, etc. Among them, polyester resins, cycloolefin resins or acrylic resins are preferred. These resins are excellent in transparency, mechanical strength, thermal stability, moisture shielding properties, etc. The above-mentioned thermoplastic resins can be used alone or in combination of two or more. In addition, optical films that can be used for polarizing plates, such as low phase difference substrates, high phase difference substrates, phase difference plates, absorption-type polarizing films, polarization selective reflection films, etc., can also be used as the first transparent substrate.
[0057] The thickness of the first transparent substrate is preferably 200 μm or less, more preferably 3 μm to 100 μm, and further preferably 5 μm to 70 μm. By setting the thickness of the first transparent substrate to 200 μm or less, the function of the PDLC layer can be fully exerted.
[0058] The total light transmittance of the first transparent substrate is preferably 30% or more, more preferably 60% or more, and even more preferably 80% or more.
[0059] The first transparent electrode layer 14 may be made of, for example, indium tin oxide (ITO), zinc oxide (ZnO), tin oxide (SnO 2 ) or other metal oxides. Preferably, a transparent electrode layer comprising ITO is formed. The transparent electrode layer comprising ITO has excellent transparency. The first transparent electrode layer can be patterned into a desired shape according to the purpose.
[0060] The light transmittance of the first transparent electrode layer is preferably 85% or more, more preferably 87% or more, and further preferably 90% or more. By using a transparent electrode layer having a light transmittance in such a range, a high light transmittance can be obtained in a transparent state. The higher the light transmittance, the more preferred it is, and its upper limit is, for example, 99%.
[0061] Preferably, the first transparent electrode layer contains crystal grains. By containing crystal grains, the light transmittance can be improved. The method for forming the crystal grains is not limited, and the crystal grains can be suitably formed by, for example, heating in the atmosphere. The area occupancy of the crystal grains in the transparent electrode layer is, for example, 30% or more, preferably 50% or more, and more preferably 80% or more. The upper limit of the area occupancy is, for example, 100%. If the area occupancy of the crystal grains is within the above range, the light transmittance can be improved. It should be noted that the area occupancy of the crystal grains can be observed by a transmission electron microscope (TEM) on the surface of the transparent electrode layer and calculated from the area ratio of the crystal grain area to the non-crystalline area.
[0062] The surface roughness Ra of the first transparent electrode layer is, for example, greater than 0.1 nm. When the surface roughness Ra of the first transparent electrode layer is less than 0.1 nm, the adhesion to the substrate may be deteriorated. The upper limit of the surface roughness Ra of the first transparent electrode layer is preferably less than 1.2 nm, more preferably less than 1.0 nm, further preferably less than 1.0 nm, and particularly preferably less than 0.8 nm. When the surface roughness Ra of the first transparent electrode layer is too large, it may become difficult to appropriately form grains. It should be noted that the surface roughness Ra in this specification refers to the arithmetic mean roughness Ra measured using an AFM (Atomic Force Microscope).
[0063] The thickness of the first transparent electrode layer is, for example, 10 nm or more, preferably 15 nm or more. When the thickness of the first transparent electrode layer is less than 10 nm, the area occupancy of the grains may decrease. The upper limit of the thickness of the first transparent electrode layer is, for example, 50 nm or less, preferably 35 nm or less, more preferably less than 30 nm, and further preferably 27 nm or less. When the thickness of the first transparent electrode layer exceeds 50 nm, the transmittance may deteriorate, and the surface roughness of the first transparent electrode layer may increase.
[0064] The first transparent electrode layer can be provided on one side of the first transparent substrate by sputtering, for example. After the metal oxide layer is formed by sputtering, annealing is performed to crystallize the metal oxide layer. Annealing is performed by heat treatment at 120° C. to 300° C. for 10 to 120 minutes, for example.
[0065] The ultraviolet blocking layer 16 shields at least a portion of ultraviolet rays, for example, shields at least a portion of light with a wavelength of 300nm to 380nm. The absorbance of the ultraviolet blocking layer at a wavelength of 350nm is, for example, 2 or more, preferably 3 or more, more preferably 4 or more, further preferably 5 or more, for example, 8 or less.
[0066] In one embodiment, when the maximum absorption wavelength on the longest wavelength side of the photopolymerization initiator contained in the PDLC layer is set to Anm, in the entire wavelength range of A-30nm to A+50nm, the absorbance of the ultraviolet blocking layer is, for example, 4.5 or more, preferably 5 or more, more preferably 5.5 or more, further preferably 6 or more, for example, 8 or less. The ultraviolet blocking layer has a high absorbance in a predetermined range including the maximum absorption wavelength on the longest wavelength side of the photopolymerization initiator, and the light resistance of the PDLC film can be suitably improved.
[0067] In one embodiment, when the maximum absorption wavelength on the longest wavelength side of the photopolymerization initiator contained in the PDLC layer is set to Ann, the absorbance of the ultraviolet blocking layer at the wavelength A+70nm is, for example, 1.8 or more, preferably 2 or more, for example, 5 or less. The ultraviolet blocking layer has a predetermined absorbance or more at a wavelength 70nm greater than the maximum absorption wavelength on the longest wavelength side of the photopolymerization initiator, so that the light resistance of the PDLC film can be suitably improved.
[0068] The ultraviolet blocking layer transmits visible light. The minimum value of the transmittance of the ultraviolet blocking layer in the wavelength range of 450 nm to 600 nm is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more.
[0069] The ultraviolet blocking layer has any appropriate structure. The ultraviolet blocking layer includes, for example, a coating layer having ultraviolet blocking ability, a resin film having ultraviolet blocking ability, an adhesive layer having ultraviolet blocking ability, etc., and may be an ultraviolet blocking layer containing only one of these, or may be an ultraviolet blocking layer containing two or more of these in a manner that the entire layer has desired optical properties.
[0070] The coating layer having ultraviolet blocking capability (ultraviolet blocking coating layer) can be directly formed on the surface of the first transparent substrate by, for example, applying an ultraviolet blocking layer forming coating liquid containing an ultraviolet absorber and / or an ultraviolet reflector to the first transparent substrate. In addition, for example, the ultraviolet blocking coating layer can also be formed by applying an ultraviolet blocking layer forming coating liquid to the surface of another substrate, and bonding it to the first transparent substrate in the form of a substrate with an ultraviolet blocking coating layer.
[0071] Examples of the resin film having an ultraviolet blocking capability (ultraviolet blocking resin film) include a resin film containing an ultraviolet absorber and / or an ultraviolet reflector, and a resin film using a nano-lamination technique.
[0072] The adhesive layer having ultraviolet blocking capability (ultraviolet blocking adhesive layer) is typically an adhesive layer containing an ultraviolet absorber and / or an ultraviolet reflector.
[0073] Any appropriate ultraviolet absorber and ultraviolet reflector can be used respectively. Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)phenylbenzotriazole, 2-(2'-hydroxy-3'-dodecyl-5'-methylphenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole-2- [(Hexyl)oxy]phenol] and other benzotriazole-based ultraviolet absorbers, acrylate-based ultraviolet absorbers such as ethyl-2-cyano-3,3'-diphenylacrylate and 2-ethylhexyl-2-cyano-3,3'-diphenylacrylate, salicylate-based ultraviolet absorbers such as phenyl salicylate and 4-tert-butylphenyl salicylate, oxalylanilide-based ultraviolet absorbers such as 2-ethoxy-2'-ethyloxalic acid dianiline and 2-ethoxy-5-tert-butyl-2'-ethyloxalic acid dianiline, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]phenol, 1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[[3,5-bis(1,1-dimethylethyl)-4-hydroxy-phenyl]methyl] and other triazine-based ultraviolet absorbers, etc. Examples of the ultraviolet reflective agent include aluminum, zinc, copper, brass, stainless steel, zinc oxide, titanium oxide, etc. The ultraviolet absorber and the ultraviolet reflective agent may be used alone or in combination of two or more.
[0074] The ultraviolet blocking layer may be a commercially available product. Examples of commercially available film products that can be used as the ultraviolet blocking layer include "TJ25UL" manufactured by FUJIFILM, "KC8UA" manufactured by Konica Minolta, and "U4-400CL" manufactured by Nexfil.
[0075] The refractive index adjusting layer can control the hue and / or transmittance of the PDLC film. The refractive index adjusting layer may be composed of a single layer or a laminate of two or more layers.
[0076] The refractive index of the refractive index adjusting layer is preferably 1.3 to 1.8, more preferably 1.35 to 1.7, and further preferably 1.38 to 1.68. In the case of a single layer, for example, when the transparent electrode layer is ITO, in order to optically relax the refractive index of ITO, it is better to say that a low refractive index is desired, and thus preferably, for example, 1.38 to 1.46. Thus, the interface reflection between the transparent substrate and the transparent electrode layer can be appropriately reduced.
[0077] The refractive index adjustment layer is formed of an inorganic substance, an organic substance, or a mixture of an inorganic substance and an organic substance. Examples of the material forming the refractive index adjustment layer include NaF, Na 3 AlF 6 、LiF、MgF 2 , CaF 2 、SiO 2 、LaF 3 , CeF 3 、Al 2 O 3 、TiO 2 、 2 O 5 、ZrO 2 、ZnO、ZnS、SiO x (x is 1.5 or more and less than 2), and inorganic substances such as acrylic resins, epoxy resins, urethane resins, melamine resins, alkyd resins, and siloxane polymers. In particular, as for the organic substance, a thermosetting resin formed by a mixture of melamine resins, alkyd resins, and organic silane condensates is preferably used.
[0078] The refractive index adjusting layer may also contain nanoparticles having an average particle diameter of 1 nm to 100 nm. By containing nanoparticles in the refractive index adjusting layer, the refractive index of the refractive index adjusting layer itself can be easily adjusted.
[0079] The content of the nanoparticles in the refractive index adjusting layer is preferably 0.1% to 90% by weight, more preferably 10% to 80% by weight, and even more preferably 20% to 70% by weight.
[0080] As the inorganic oxide forming nanoparticles, for example, silicon oxide (silicon dioxide), hollow nano silicon dioxide, titanium oxide, aluminum oxide, zinc oxide, tin oxide, zirconium oxide, niobium oxide etc. can be enumerated. Among these, silicon oxide (silicon dioxide), titanium oxide, aluminum oxide, zinc oxide, tin oxide, zirconium oxide, niobium oxide are preferred. These can be used alone or in combination of two or more.
[0081] The thickness of the refractive index adjustment layer is preferably 10 nm to 200 nm, more preferably 20 nm to 150 nm, and further preferably 30 nm to 130 nm. If the thickness of the refractive index adjustment layer is too small, it is difficult to form a continuous film. In addition, if the thickness of the refractive index adjustment layer is too large, there is a tendency that the transparency in a transparent state is reduced or cracks are easily generated.
[0082] The refractive index adjusting layer can be formed by using the above-mentioned materials by a wet method, a coating method such as a gravure coating method or a bar coating method, a vacuum deposition method, a sputtering method, an ion plating method, or the like.
[0083] The first conductive substrate is not limited to the configuration shown in the drawings. Figure 2 As shown, a first conductive substrate 10a including a first transparent substrate 12 also serving as an ultraviolet blocking layer 16 and a first transparent electrode layer 14 disposed on one side thereof can be used. The first transparent substrate 12 is, for example, a polymer film containing an ultraviolet absorber, and the ultraviolet absorber and the polymer film are as described above.
[0084] A-1-2. PDLC layer
[0085] The PDLC layer 20 includes a polymer matrix 22, liquid crystal compound droplets (liquid crystal droplets) 24 dispersed in the polymer matrix 22, and a photopolymerization initiator 26. Figure 1 As shown, the PDLC layer 20 has a first region A and a second region B. The liquid crystal droplets 24 in the first region A include a non-oriented liquid crystal polymer 24c and a non-polymerizable liquid crystal compound 24b, and the liquid crystal droplets 24 in the second region B include a polymerizable liquid crystal compound 24a and a non-polymerizable liquid crystal compound 24b. The first region A and the second region B can be formed in any appropriate pattern according to the desired design of the PDLC film.
[0086] The polymer matrix can be composed of any appropriate resin. The polymer matrix forming resin can be appropriately selected according to light transmittance, the refractive index of the liquid crystal compound, and the adhesion with the conductive substrate. For example, water-soluble resins or water-dispersible resins such as urethane resins, polyvinyl alcohol resins, polyethylene resins, polypropylene resins, and acrylic resins can be preferably used. The polymer matrix forming resin can be used alone or in combination.
[0087] The content ratio of the polymer matrix in the PDLC layer is, for example, 30% to 69.9% by weight, preferably 35% to 65% by weight, and more preferably 40% to 60% by weight in both the first region and the second region. If the content ratio of the polymer matrix is within this range, it is possible to obtain effects such as being able to exert a good dimming function with a moderate operating voltage, being able to obtain good mechanical strength, and preventing liquid crystal from leaking from the end.
[0088] As the non-polymerizable liquid crystal compound, any appropriate liquid crystal compound can be used. Preferably, a liquid crystal compound having a birefringence Δn (=ne-no, ne is the refractive index in the long axis direction of the liquid crystal compound molecule, no is the refractive index in the short axis direction of the liquid crystal compound molecule) of 0.05 to 0.50 at a wavelength of 589 nm, and more preferably a liquid crystal compound having a birefringence Δn of 0.10 to 0.45 can be used.
[0089] The dielectric anisotropy of the non-polymerizable liquid crystal compound may be positive or negative. The non-polymerizable liquid crystal compound may be, for example, a nematic, smectic, or cholesteric liquid crystal compound. Nematic liquid crystal compounds are preferably used because they can achieve excellent transparency in a transparent state.
[0090] As nematic liquid crystal compounds, biphenyl compounds, phenyl benzoate compounds, cyclohexylbenzene compounds, azoxybenzene compounds, azobenzene compounds, azomethine compounds, terphenyl compounds, biphenyl benzoate compounds, cyclohexylbiphenyl compounds, phenylpyridine compounds, cyclohexylpyrimidine compounds, cholesterol compounds, fluorine compounds, etc. can be cited. These low molecular liquid crystal compounds can be used alone or in combination.
[0091] The polymerizable liquid crystal compound can be appropriately selected according to light transmittance, compatibility with non-polymerizable liquid crystal compounds, etc. The polymerizable liquid crystal compound can also be a cross-linked type with more than two functions. For polymerizable liquid crystal compounds, for example, polymerizable liquid crystal original compounds described in Japanese Patent Table 2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171 and GB2280445 can be used. As a specific example of such a polymerizable liquid crystal original compound, for example, the trade name LC242 of BASF can be cited. For polymerizable liquid crystal compounds, for example, nematic liquid crystal monomers are preferably used.
[0092] Liquid crystal polymers are typically polymers of the above-mentioned polymerizable liquid crystal compounds. A polymer can be formed by polymerization of a polymerizable liquid crystal compound, and a network structure can be formed by cross-linking, but these are non-liquid crystal. Therefore, in liquid crystal polymers, for example, transitions to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes, which are unique to liquid crystal compounds, do not occur.
[0093] The liquid crystal polymer is typically present in a non-oriented state in the liquid crystal droplets. Since the liquid crystal polymer in the liquid crystal droplets is in a non-oriented state, the first region can maintain a high haze (eg, 40% to 100%, preferably 60% to 100%) even when a voltage is applied.
[0094] The total content ratio of the non-polymerizable liquid crystal compound and the liquid crystal polymer in the first region is, for example, 30% by weight to 69.9% by weight, preferably 35% by weight to 65% by weight, and more preferably 40% by weight to 60% by weight. In addition, the weight content ratio of the non-polymerizable liquid crystal compound and the liquid crystal polymer in the first region (non-polymerizable liquid crystal compound: liquid crystal polymer) is, for example, 99:1 to 70:30, and preferably 95:5 to 80:20. In addition, the total content ratio of the polymer matrix, the non-polymerizable liquid crystal compound, and the liquid crystal polymer in the first region can be, for example, 90% by weight to 99.9% by weight, and preferably 95% by weight to 99.9% by weight.
[0095] The total content ratio of the non-polymerizable liquid crystal compound and the polymerizable liquid crystal compound in the second region is, for example, 30% by weight to 69.9% by weight, preferably 35% by weight to 65% by weight, and more preferably 40% by weight to 60% by weight. In addition, the weight content ratio of the non-polymerizable liquid crystal compound and the polymerizable liquid crystal compound in the second region (non-polymerizable liquid crystal compound: polymerizable liquid crystal compound) is, for example, 99:1 to 70:30, and preferably 95:5 to 80:20. In addition, the total content ratio of the polymer matrix, the non-polymerizable liquid crystal compound, and the polymerizable liquid crystal compound in the second region can be, for example, 90% by weight to 99.9% by weight, and preferably 95% by weight to 99.9% by weight.
[0096] As the photopolymerization initiator, for example, an initiator that can initiate polymerization of the polymerizable liquid crystal compound by ultraviolet irradiation can be used. Specifically, benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzil-based polymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators can be cited.
[0097] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime-based photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin-based photopolymerization initiators include benzoin. Examples of benzyl-based photopolymerization initiators include benzyl. Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, and the like. Examples of ketal-based photopolymerization initiators include benzyldimethylketal, and the like. Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0098] The photopolymerization initiator has a maximum absorption wavelength in the range of, for example, 300 nm to 340 nm, preferably 320 nm to 340 nm. By using such a photopolymerization initiator, the PDLC film of the embodiment of the present invention can be easily manufactured, and the effect of preventing the formation of unintended liquid crystal polymers caused by the ultraviolet blocking layer can be appropriately obtained.
[0099] The content ratio of the photopolymerization initiator in the PDLC layer is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 5 parts by weight, based on 100 parts by weight of the total of the polymerizable liquid crystal compound and the liquid crystal polymer.
[0100] As described in detail in item B, regarding the PDLC layer having the first region and the second region, in a predetermined region of the PDLC layer containing liquid crystal droplets containing a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound, it can be formed by polymerizing the polymerizable liquid crystal compound to form a liquid crystal polymer, in which case the predetermined region becomes the first region and the other regions become the second region. At this time, unreacted polymerizable liquid crystal compounds may remain in the liquid crystal droplets in the first region. The content ratio of the unreacted polymerizable liquid crystal compound in the first region is, for example, 3% by weight or less, preferably 1% by weight or less. In addition, it is preferred that there is substantially no liquid crystal polymer in the liquid crystal droplets in the second region. The content ratio of the liquid crystal polymer in the second region is, for example, 3% by weight or less, preferably 1% by weight or less.
[0101] The average particle size of the liquid crystal droplets may be, for example, 0.3µm to 9µm, preferably 0.4µm to 8µm. If the average particle size of the liquid crystal droplets is too small, the size of the liquid crystal droplets is smaller than the wavelength of light, so that light will pass through the liquid crystal droplets without scattering, resulting in a problem that sufficient haze cannot be obtained. In addition, if the average particle size is too large, the size of the liquid crystal droplets is much larger than the wavelength of light, so that sufficient haze cannot be obtained. It should be noted that the average particle size of the liquid crystal droplets in the above-mentioned PDLC layer is the volume average particle size of the liquid crystal droplets when observed from a direction perpendicular to the main surface of the PDLC film.
[0102] The thickness of the PDLC layer is typically 2 µm to 40 µm, preferably 3 µm to 35 µm, and more preferably 4 µm to 30 µm.
[0103] A-1-3. Second conductive substrate
[0104] The second conductive substrate 30 typically includes a second transparent substrate 32 and a second transparent electrode layer 34 provided on one side thereof. The second conductive substrate 30 may include a hard coating layer on one or both sides of the second transparent substrate 32 as required, and may include a refractive index adjustment layer between the second transparent substrate 32 and the second transparent electrode layer 34.
[0105] The surface resistance value of the second transparent electrode layer-side surface of the second conductive substrate is preferably 1 Ω / □ to 1000 Ω / □, more preferably 5 Ω / □ to 300 Ω / □, and further preferably 10 Ω / □ to 200 Ω / □.
[0106] The haze of the second conductive substrate is preferably 20% or less, more preferably 10% or less, and further preferably 0.1% to 10%.
[0107] The total light transmittance of the second conductive substrate is preferably 30% or more, more preferably 60% or more, and even more preferably 80% or more.
[0108] The same descriptions as those for the first transparent substrate and the first transparent electrode layer can be applied to the second transparent substrate and the second transparent electrode layer, respectively.
[0109] A-2. PDLC film of the second embodiment
[0110] Figure 3 (a) is a schematic top view of an example of a PDLC film according to the second embodiment of the present invention, (b) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when no voltage is applied, and (c) is a schematic cross-sectional view illustrating the state of the PDLC film shown in (a) when voltage is applied. The PDLC film 100b sequentially comprises: a first conductive substrate 10 including an ultraviolet blocking layer 16, a PDLC layer 20 including a polymer matrix 22 and liquid crystal droplets 24 dispersed in the polymer matrix 22 and a photopolymerization initiator 26, and a second conductive substrate 30. The PDLC layer 20 has a first region A and a second region B in which the haze change amount after voltage is applied is different when viewed from above. The liquid crystal droplets 24 in the second region B include a polymerizable liquid crystal compound 24a and a non-polymerizable liquid crystal compound 24b. The liquid crystal droplets 24 in the first region A include a liquid crystal polymer 24c and a non-polymerizable liquid crystal compound 24b. Typically, the liquid crystal polymer 24 c is oriented in a predetermined direction (in the example of the figure, a direction perpendicular to the main surfaces of the first conductive substrate 10 and the second conductive substrate 30 ). The photopolymerization initiator 26 is dispersed in the PDLC layer 20 , and at least a portion thereof is also contained in the liquid crystal droplets 24 .
[0111] like Figure 3 As shown in (b), in the PDLC film 100b when no voltage is applied, the polymerizable liquid crystal compound 24a and the non-polymerizable liquid crystal compound 24b in the liquid crystal droplet 24 in the second region B are both in a non-oriented state, so that the transmitted light is scattered. On the other hand, in the first region A, the non-polymerizable liquid crystal compound 24b is oriented along the orientation direction of the liquid crystal polymer 24c, and as a result, the scattering of the transmitted light is suppressed. Therefore, in the PDLC film 100b, the first region A can be in a transparent state, and the second region B can be in a scattering state.
[0112] On the other hand, Figure 3As shown in (c), in the PDLC film 100b when voltage is applied, the polymerizable liquid crystal compound 24a and the non-polymerizable liquid crystal compound 24b in the liquid crystal droplet 24 in the second region B are oriented in a direction perpendicular to the main surfaces of the first conductive substrate 10 and the second conductive substrate 30, and the scattering of the transmitted light is suppressed, resulting in a reduction in haze. On the other hand, in the first region A, the orientation of the polymerizable liquid crystal compound 24b does not change significantly due to the orientation restriction brought about by the liquid crystal polymer 24c, and thus the scattering of the transmitted light is still suppressed. Therefore, the amount of change in haze after voltage application in the first region is smaller than that in the second region, and the difference between the haze in the first region and the haze in the second region is reduced by the application of voltage.
[0113] As described above, when no voltage is applied, the PDLC film 100b presents an appearance in which the first region is transparent and the second region is turbid. The haze of the second region is greatly reduced by the voltage application, and the two regions become transparent. As a result, the main surface as a whole can present a transparent appearance. Therefore, the PDLC film 100b can present different appearances by switching between the application and non-application of voltage.
[0114] The voltage applied to the PDLC film during voltage application is a voltage (operation voltage) at which the PDLC film can be operated, and may be, for example, 5V to 200V, and preferably 10V to 100V.
[0115] The haze of the first region when the voltage is not applied is, for example, 1% to 20%, preferably 1% to 10%. The haze of the first region when the voltage is applied is, for example, 1% to 20%, preferably 1% to 10%. The amount of change in the haze of the first region after the voltage is applied (|haze when the voltage is not applied - haze when the voltage is applied|) is, for example, 0% to 20%, preferably 0% to 10%.
[0116] The haze of the second region when the voltage is not applied is, for example, 50% to 100%, preferably 70% to 100%. The haze of the second region when the voltage is applied is, for example, 1% to 20%, preferably 1% to 10%. The amount of change in the haze of the second region after the voltage is applied (|haze when the voltage is not applied - haze when the voltage is applied|) is, for example, 30% to 99%, preferably 60% to 99%.
[0117] The amount of change in haze of the first region after voltage application is smaller than the amount of change in haze of the second region after voltage application, and the difference is, for example, 10% to 99%, preferably 30% to 99%.
[0118] The total light transmittance of the first region when no voltage is applied is, for example, 70% to 95%, preferably 80% to 90%. The total light transmittance of the first region when voltage is applied is, for example, 70% to 95%, preferably 80% to 90%.
[0119] The total light transmittance of the second region when no voltage is applied is, for example, 50% to 95%, preferably 60% to 90%. The total light transmittance of the second region when voltage is applied is, for example, 70% to 95%, preferably 80% to 90%.
[0120] At 30°C and 55% RH, the first conductive substrate was exposed to 120 W / m 2 The haze change Va (|haze when voltage is applied - haze when voltage is not applied|) of the second area after applying voltage (e.g., 50V) 125 hours after (300nm-400nm) irradiation with xenon light and the haze change Vb of the second area before irradiation after applying voltage (e.g., 50V) satisfy the relationship of (Vb-Va) / Vb×100≤5, and preferably satisfy the relationship of (Vb-Va) / Vb×100≤3.
[0121] The thickness of the PDLC film is, for example, 30 μm to 250 μm, and preferably 50 μm to 150 μm.
[0122] Regarding the PDLC film of the second embodiment, the first conductive substrate and the second conductive substrate can be respectively applied to the same description as the first conductive substrate and the second conductive substrate in the PDLC film of the first embodiment. In addition, the PDLC layer can be applied to the same description as the PDLC layer in the PDLC film of the first embodiment, except that the liquid crystal polymer contained in the liquid crystal droplets in the first region is oriented in a predetermined direction.
[0123] In the first region of the PDLC layer, the liquid crystal polymer contained in the liquid crystal droplet is oriented in a predetermined direction. The liquid crystal polymer is preferably oriented in a substantially perpendicular direction to the main surfaces of the first conductive substrate and the second conductive substrate to form an angle of, for example, 90°±5°, preferably 90°±3°. Since the liquid crystal polymer in the liquid crystal droplet is oriented in a predetermined direction, the first region can maintain a low haze (for example, 1% to 20%, preferably 1% to 10%) even when no voltage is applied.
[0124] B. Method for manufacturing polymer dispersed liquid crystal film
[0125] The PDLC film described in the section A can be produced by any appropriate production method.
[0126] For example, the PDLC film can be manufactured by the following manufacturing method (manufacturing method A), which includes the following steps:
[0127] (Step A1) preparing an unpatterned PDLC film, the unpatterned PDLC film comprising, in order: a first conductive substrate; a PDLC layer comprising a polymer matrix and liquid crystal droplets dispersed in the polymer matrix and a photopolymerization initiator, the liquid crystal droplets comprising a non-polymerizable liquid crystal compound and the polymerizable liquid crystal compound; and a second conductive substrate; and
[0128] (Step A2) irradiating the second conductive substrate side of the unpatterned PDLC film with active energy rays in a predetermined pattern to polymerize the polymerizable liquid crystal compound to form a first region containing liquid crystal droplets, wherein the liquid crystal droplets contain a liquid crystal polymer that is a polymer of the polymerizable liquid crystal compound and the non-polymerizable liquid crystal compound.
[0129] According to the manufacturing method of the PDLC film, a PDLC layer having the following first region and second region can be formed, wherein the liquid crystal droplets of the first region contain a liquid crystal polymer and a non-polymerizable liquid crystal compound, and the liquid crystal droplets of the second region contain a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound, and as a result, the PDLC film described in item A can be suitably obtained. It should be noted that in the description of the manufacturing method of the PDLC film, the PDLC layer or PDLC film having the first region and the second region formed therein is sometimes referred to as a patterned PDLC layer or a patterned PDLC film, and the PDLC layer or PDLC film having the first region and the second region not formed therein is sometimes referred to as an unpatterned PDLC layer or an unpatterned PDLC film.
[0130] In one embodiment, the active energy ray irradiation of step A2 is performed without applying a voltage between the first conductive substrate and the second conductive substrate. In another embodiment, the active energy ray irradiation of step A2 is performed with applying a voltage between the first conductive substrate and the second conductive substrate.
[0131] B-1. Process A1
[0132] In step A1, an unpatterned PDLC film is prepared, which contains in sequence: a first conductive substrate; a PDLC layer comprising a polymer matrix and liquid crystal droplets dispersed in the above polymer matrix and a photopolymerization initiator, the liquid crystal droplets comprising a non-polymerizable liquid crystal compound and the above-mentioned polymerizable liquid crystal compound; and a second conductive substrate.
[0133] Step A1 includes, for example:
[0134] (Step A1-1) applying a coating liquid containing a polymer matrix-forming resin, a non-polymerizable liquid crystal compound, a polymerizable liquid crystal compound, a photopolymerization initiator, and a solvent on either the first conductive substrate or the second conductive substrate to obtain a coating layer;
[0135] (Step A1-2) drying the coating layer to obtain an unpatterned PDLC layer, wherein the unpatterned PDLC layer comprises a polymer matrix, and liquid crystal droplets and a photopolymerization initiator dispersed in the polymer matrix, wherein the liquid crystal droplets comprise the non-polymerizable liquid crystal compound and the polymerizable liquid crystal compound;
[0136] (Step A1-3) Another substrate is stacked on the unpatterned PDLC layer.
[0137] In step A1-1, a coating liquid containing a polymer matrix-forming resin, a non-polymerizable liquid crystal compound, a polymerizable liquid crystal compound, a photopolymerization initiator, and a solvent is applied on either the first conductive substrate or the second conductive substrate to obtain a coating layer.
[0138] The coating liquid is preferably an emulsion in which liquid crystal particles containing a non-polymerizable liquid crystal compound and a polymerizable liquid crystal compound are dispersed in a solvent (hereinafter sometimes referred to as an "emulsion coating liquid"). In one embodiment, the coating liquid is an emulsion coating liquid in which polymer matrix-forming resin particles and liquid crystal particles containing a non-polymerizable liquid crystal compound and a polymerizable liquid crystal compound are dispersed in a solvent. The emulsion coating liquid may further contain a photopolymerization initiator and may further contain any appropriate additives depending on the purpose.
[0139] As for the solvent, water or a mixed solvent of water and a water-miscible organic solvent can be preferably used. As the water-miscible organic solvent, C1-3 alcohol, acetone, DMSO, etc. can be mentioned. The non-polymerizable liquid crystal compound, the polymerizable liquid crystal compound and the polymer matrix forming resin are as described in item A. As arbitrary additives, dispersants, leveling agents, cross-linking agents, etc. can be mentioned.
[0140] The content ratio of the liquid crystal compound in the solid component of the coating liquid (the total content ratio of the non-polymerizable liquid crystal compound and the polymerizable liquid crystal compound) can be, for example, 30% to 69.9% by weight, preferably 35% to 65% by weight, and more preferably 40% to 60% by weight.
[0141] The weight ratio of the non-polymerizable liquid crystal compound to the polymerizable liquid crystal compound in the coating liquid (non-polymerizable liquid crystal compound:polymerizable liquid crystal compound) is preferably 99:1 to 70:30, and more preferably 95:5 to 80:20.
[0142] The content ratio of the polymer matrix-forming resin in the solid content of the coating liquid may be, for example, 30% to 69.9% by weight, preferably 35% to 65% by weight, and more preferably 40% to 60% by weight.
[0143] The weight ratio of the content of the liquid crystal compound (the total content of the non-polymerizable liquid crystal compound and the polymerizable liquid crystal compound) to the content of the polymer matrix-forming resin in the coating liquid (liquid crystal compound: polymer matrix-forming resin) may be, for example, 30:70 to 70:30, preferably 35:65 to 65:35, and more preferably 40:60 to 60:40. In addition, the total content of the polymer matrix-forming resin, the non-polymerizable liquid crystal compound, and the polymerizable liquid crystal compound in the solid content of the coating liquid may be, for example, 90% by weight to 99.9% by weight, and preferably 95% by weight to 99.9% by weight.
[0144] The average particle size of the liquid crystal particles is preferably 0.3 µm or more, more preferably 0.4 µm or more. In addition, the average particle size of the liquid crystal particles is preferably 9 µm or less, more preferably 8 µm or less. If the average particle size of the liquid crystal particles is within this range, the average particle size of the liquid crystal droplets in the PDLC layer can be set to a desired range. It should be noted that the average particle size of the liquid crystal particles is a volume average particle size.
[0145] The average particle size of the liquid crystal particles preferably has a narrow particle size distribution. The coefficient of variation (CV value) of the average particle size of the liquid crystal particles may be, for example, less than 0.40, preferably less than 0.35, and more preferably less than 0.30. In one embodiment, an emulsion coating liquid that substantially does not contain liquid crystal particles with a particle size of less than 0.3µm or greater than 9µm (e.g., an emulsion coating liquid in which the volume of liquid crystal particles with a particle size of less than 0.3µm or greater than 9µm is less than 10% of the total volume of the liquid crystal particles) may be used.
[0146] The average particle size of the polymer matrix-forming resin particles is preferably 10 nm to 500 nm, more preferably 30 nm to 300 nm, and further preferably 50 nm to 200 nm. Two or more resin particles having different types of resins and / or average particle sizes may also be used. The average particle size of the polymer matrix-forming resin particles means the volume average median particle size, and can be measured using a dynamic light scattering particle size distribution measuring device.
[0147] The photopolymerization initiator and its content are as described in the section A.
[0148] Examples of the dispersant include anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants, etc. The content of the dispersant is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the emulsion coating liquid.
[0149] Examples of the leveling agent include acrylic leveling agents, fluorine leveling agents, silicone leveling agents, etc. The content of the leveling agent is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the emulsion coating liquid.
[0150] Examples of the crosslinking agent include aziridine crosslinking agents, isocyanate crosslinking agents, etc. The content of the crosslinking agent is preferably 0.5 to 10 parts by weight, more preferably 0.8 to 5 parts by weight, based on 100 parts by weight of the emulsion coating liquid.
[0151] The emulsion coating liquid can be prepared, for example, by mixing a resin emulsion or a resin particle dispersion containing polymer matrix-forming resin particles, a liquid crystal emulsion containing liquid crystal particles, a photopolymerization initiator, and any additives (e.g., a dispersant, a leveling agent, a crosslinking agent). A solvent may be further added during the mixing as required. Alternatively, the emulsion coating liquid may be prepared by adding a non-polymerizable liquid crystal compound, a polymerizable liquid crystal compound, a water-dispersible resin, a photopolymerization initiator, and any additives to a solvent and dispersing them mechanically.
[0152] The above-mentioned resin emulsion and liquid crystal emulsion can be prepared by, for example, mechanical emulsification, microchannel method, membrane emulsification method, etc. Among them, the liquid crystal emulsion is preferably prepared by membrane emulsification. According to the membrane emulsification method, an emulsion with a uniform particle size distribution can be suitably obtained. For details of the membrane emulsification method, reference can be made to the disclosures of Japanese Patent Laid-Open No. 4-355719, Japanese Patent Laid-Open No. 2015-40994 (these are cited as references in this specification), etc.
[0153] The solid content concentration of the emulsion coating liquid may be, for example, 20% to 60% by weight, and preferably 30% to 50% by weight.
[0154] The viscosity of the emulsion coating liquid can be appropriately adjusted to be suitable for coating on the substrate. The viscosity of the emulsion coating liquid during coating is preferably 20mPas~400mPas, more preferably 30mPas~300mPas, and further preferably 40mPas~200mPas. When the viscosity is less than 20mPas, when the solvent is dried, the convection of the solvent becomes obvious, and the thickness of the PDLC layer may become unstable. In addition, when the viscosity exceeds 400mPas, the liquid beads of the emulsion coating liquid may be unstable. The viscosity of the emulsion coating liquid can be measured by, for example, a rheometer MCR302 manufactured by Anton Paar. The viscosity here uses the shear viscosity value under the conditions of 20°C and a shear rate of 1000 (1 / second).
[0155] The emulsion coating liquid is typically applied to the transparent electrode layer side surface of the first conductive substrate or the second conductive substrate. These substrates are as described in the section A.
[0156] As for the coating method, any appropriate method can be adopted. For example, roll coating, spin coating, wire rod coating, dip coating, die coating, curtain coating, spray coating, blade coating (notch wheel coating, etc.) and the like can be cited. Among them, roll coating is preferred. For example, regarding coating using a roll coating method using a slit coating die, reference can be made to the records of Japanese Patent Publication No. 2019-5698.
[0157] The thickness of the coating layer is preferably 3 to 40 μm, more preferably 4 to 30 μm, and even more preferably 5 to 20 μm. Within this range, a PDLC layer having excellent thickness uniformity can be obtained.
[0158] In step A1-2, the coating layer is dried to obtain an unpatterned PDLC layer including a polymer matrix, liquid crystal droplets dispersed in the polymer matrix, and a photopolymerization initiator. The solvent is removed from the coating layer by drying, and the polymer matrix-forming resin particles are fused to each other, thereby forming a PDLC layer having a structure in which liquid crystal droplets including a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound and a photopolymerization initiator are dispersed in the polymer matrix.
[0159] The coating layer may be dried by any appropriate method. Specific examples of the drying method include heating drying and hot air drying. When the emulsion coating liquid contains a crosslinking agent, a crosslinked structure of the polymer matrix may be formed during drying.
[0160] The drying temperature is preferably 20° C. to 150° C., and more preferably 25° C. to 80° C. The drying time is preferably 1 minute to 100 minutes, and more preferably 2 minutes to 10 minutes.
[0161] In step A1-3, another substrate is stacked on the unpatterned PDLC layer. Thus, an unpatterned PDLC film having the first conductive substrate, the unpatterned PDLC layer, and the second conductive substrate in this order can be obtained.
[0162] The lamination of the first conductive substrate or the second conductive substrate on the PDLC layer is performed in a manner such that the transparent electrode layer side faces the PDLC layer. From the viewpoint of obtaining sufficient adhesion, the lamination is preferably performed using a laminator while applying a lamination pressure of 0.006MPa / m to 7MPa / m, more preferably 0.06MPa / m to 0.7MPa / m.
[0163] B-2. Process A2
[0164] In step A2, active energy rays are irradiated in a predetermined pattern from the second conductive substrate side of the unpatterned PDLC film to polymerize the polymerizable liquid crystal compound to form a first region containing liquid crystal droplets, the liquid crystal droplets containing a liquid crystal polymer as a polymer of the polymerizable liquid crystal compound and the non-polymerizable liquid crystal compound. Specifically, in the region irradiated with active energy rays (irradiated region), the polymerizable liquid crystal compound in the liquid crystal droplets polymerizes to generate a liquid crystal polymer, and as a result, liquid crystal droplets containing a liquid crystal polymer and a non-polymerizable liquid crystal compound are formed. On the other hand, in the region not irradiated with active energy rays (non-irradiated region), the polymerizable liquid crystal compound exists in an unreacted state, and as a result, the liquid crystal droplets contain a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound. Therefore, the irradiated region of the PDLC layer becomes the first region A containing liquid crystal droplets containing a liquid crystal polymer and a non-polymerizable liquid crystal compound, and the non-irradiated region becomes the second region B containing liquid crystal droplets containing a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound. It should be noted that the content ratio of polymerizable liquid crystal compounds to non-polymerizable liquid crystal compounds in the droplets in the non-irradiated area can roughly correspond to the content ratio at the initial stage of formation of the liquid crystal droplets, that is, the content ratio of polymerizable liquid crystal compounds to non-polymerizable liquid crystal compounds in the coating liquid.
[0165] The irradiation of the active energy ray is carried out through a photomask of a predetermined pattern. As for the active energy ray, ultraviolet rays, infrared rays, X-rays, α rays, β rays and electron beams can be used. Among them, ultraviolet rays are preferred. In addition, the active energy ray is preferably a collimated light with high straightness from the irradiation source.
[0166] The ultraviolet irradiation conditions can be appropriately set according to the type of polymerizable liquid crystal compound, the transmittance of the second conductive substrate, the absorption wavelength of the photopolymerization initiator, etc. The irradiation intensity can be, for example, 0.1 mW / cm 2 ~1000mW / cm 2 , preferably 1 mW / cm 2 ~100mW / cm 2 The irradiation dose can be, for example, 10 mJ / cm 2 ~10000mJ / cm 2 , preferably 100 mJ / cm 2 ~5000mJ / cm 2 The irradiation temperature may be, for example, -20°C to 80°C, and preferably -20°C to 60°C.
[0167] Figure 4 and Figure 5 Each of the diagrams is a schematic diagram for explaining an example of irradiation with active energy rays in the method for producing a PDLC film according to an embodiment of the present invention. Figure 4In the embodiment shown, the active energy ray irradiation is performed through the photomask 40 and without applying a voltage between the first conductive substrate 10 and the second conductive substrate 30. According to the present embodiment, in the liquid crystal droplets 24 in the irradiation area of the PDLC layer 20, the polymerizable liquid crystal compound 24a is polymerized in a non-oriented state, and the formed liquid crystal polymer 24c is also in a non-oriented state. Therefore, according to the present embodiment, the PDLC film of the first embodiment described in the item A-1 can be suitably obtained.
[0168] exist Figure 5 In the embodiment shown, the active energy ray irradiation is performed through the photomask 40 and in a state where a voltage is applied between the first conductive substrate 10 and the second conductive substrate 30. According to this embodiment, in the liquid crystal droplets 24 in the irradiation area of the PDLC layer 20, the polymerizable liquid crystal compound 24a is polymerized in a state where it is oriented in a predetermined direction (in the example of the figure, a direction perpendicular to the main surfaces of the first conductive substrate 10 and the second conductive substrate 30) along the electric field, thereby forming a liquid crystal polymer 24c in which the orientation is fixed. Therefore, according to this embodiment, the PDLC film of the second embodiment described in item A-2 can be appropriately obtained. It should be noted that as long as the desired orientation (in other words, the desired haze for the first area) is achieved, the voltage applied during the active energy ray irradiation is not limited, and can be, for example, 10V to 200V, preferably 20V to 100V.
[0169] In one embodiment, the active energy ray irradiation is performed using a photomask having a plurality of light-transmitting portions with different aperture ratios, whereby the first region can be formed in a ratio corresponding to the aperture ratio in the region corresponding to each light-transmitting portion. Therefore, in the obtained PDLC film, the region corresponding to each light-transmitting portion can show a haze corresponding to the aperture ratio as a whole.
[0170] For example, by using a photomask whose aperture ratio increases continuously from the right end to the left end, and irradiating with active energy rays in a state where no voltage is applied, a PDLC film having the following appearance can be obtained: when no voltage is applied, the entire surface is in a scattered state, and when a voltage is applied, the haze increases continuously from the right end to the left end. For another example, by using a photomask whose aperture ratio increases continuously from the right end to the left end, and irradiating with active energy rays in a state where a voltage is applied, a PDLC film having the following appearance can be obtained: when a voltage is applied, the entire surface is in a transparent state, and when a voltage is not applied, the haze decreases continuously from the right end to the left end.
[0171] In the above-mentioned method A for manufacturing the PDLC film, an unpatterned PDLC film is prepared, which sequentially includes a first conductive substrate, an unpatterned PDLC layer and a second conductive substrate, and active energy rays are irradiated from the second conductive substrate side of the unpatterned PDLC film, but the above-mentioned method for manufacturing the PDLC film is not limited to this embodiment.
[0172] For example, the PDLC film can be manufactured by a manufacturing method (manufacturing method B) comprising the following steps in sequence: preparing an unpatterned PDLC film comprising a second conductive substrate, an unpatterned PDLC layer, and a second conductive substrate in sequence; irradiating the unpatterned PDLC film with active energy rays in a predetermined pattern from any side of the unpatterned PDLC film; and providing an ultraviolet blocking layer on the outer side of any second conductive substrate. The irradiation with active energy rays is performed in a state where no voltage is applied between the two substrates or in a state where a voltage is applied between the two substrates.
[0173] For example, the PDLC film can be manufactured by a manufacturing method (manufacturing method C) comprising the following steps in sequence: preparing an unpatterned PDLC film comprising a second conductive substrate, an unpatterned PDLC layer, and a second conductive substrate in sequence; providing an ultraviolet blocking layer on the outside of any second conductive substrate; and irradiating the second conductive substrate with active energy rays in a predetermined pattern from the side of the second conductive substrate where the ultraviolet blocking layer is not provided. The irradiation with active energy rays is performed in a state where no voltage is applied between the two substrates or in a state where a voltage is applied between the two substrates.
[0174] The second conductive substrate provided with a UV blocking layer can be equivalent to the first conductive substrate, so even through manufacturing method B and manufacturing method C, a patterned PDLC film containing the first conductive substrate including the UV blocking layer, the patterned PDLC layer and the second conductive substrate in sequence can be obtained.
[0175] C. Variations
[0176] C-1. Modification 1
[0177] Figure 6 1 is a schematic cross-sectional view for explaining the structure of a modified example of the PDLC film according to the embodiment of the present invention. The PDLC film 100c sequentially comprises: a first conductive substrate 10 including a first ultraviolet blocking layer 16, a PDLC layer 20 including a polymer matrix (not shown) and liquid crystal droplets (not shown) dispersed in the polymer matrix and a photopolymerization initiator (not shown), and a second conductive substrate 30 including a second ultraviolet blocking layer 36. The PDLC layer 20 is as follows: Figure 1 or Figure 3The patterned PDLC layer shown has a first region and a second region. That is, the PDLC film 100c is different from the PDLC film 100a or 100b in that the second conductive substrate 30 includes a second ultraviolet blocking layer 36. The PDLC film 100c is provided with ultraviolet blocking layers on both sides of the patterned PDLC layer, so it is more suitable for improving light resistance.
[0178] C-2. Modification 2
[0179] Figure 7 100d is a schematic cross-sectional view for explaining the structure of another modified example of the PDLC film according to the embodiment of the present invention. The PDLC film 100d sequentially comprises: a first conductive substrate 10 including a first ultraviolet blocking layer 16, a PDLC layer 20 including a polymer matrix (not shown) and liquid crystal droplets (not shown) dispersed in the polymer matrix and a photopolymerization initiator (not shown), and a second conductive substrate 30 including a reflective layer 38. The PDLC layer 20 is as follows: Figure 1 or Figure 3 The patterned PDLC layer shown has a first region and a second region. That is, the PDLC film 100d is different from the PDLC film 100a or 100b in that the second conductive substrate 30 includes a reflective layer 38 .
[0180] According to the PDLC film 100d, light incident on the PDLC layer 20 in a scattered state from the first conductive substrate 10 side is reflected by the reflective layer 38 and scattered by the PDLC layer 20, and as a result, is emitted from the first conductive substrate 10 side in the form of light containing a large amount of scattered reflection components. On the other hand, light incident on the PDLC layer 20 in a transparent state (non-scattering state) from the first conductive substrate 10 side is suppressed from being scattered by the PDLC layer 20, and is reflected by the reflective layer 38, and as a result, is emitted from the conductive transparent substrate 10 side in the form of light containing a large amount of regular reflection components. As a result, the area in the scattered state can present an appearance with less gloss (matte appearance), and the area in the transparent state can present an appearance with gloss (metallic appearance). Therefore, by forming the first area and the second area in a desired pattern and switching the voltage application state, the following states can be switched: a state in which the entire main surface has a glossy appearance or a less glossy appearance, and a state in which only a partial area has a glossy appearance or a less glossy appearance.
[0181] In the example of the figure, the second conductive substrate 30 has a second transparent electrode layer 34, a second transparent substrate 32 and a reflective layer 38 in this order. The configuration of the second conductive substrate 30 including the reflective layer 38 is not limited to the example of the figure. Figure 8 (a) shows a second conductive substrate 30a including a reflective layer 38, a second transparent electrode layer 34 and a second transparent substrate 32 in this order. Figure 8 (b) shows a second conductive substrate 30b having a second transparent substrate 32 and a conductive reflective layer 35 provided on one side thereof (PDLC layer side). Here, the conductive reflective layer means a layer that can perform both the function of a reflective layer and the function of an electrode layer. The reflective layer can be used in the form of a reflective film with a protective layer provided on one or both surfaces thereof.
[0182] The reflective layer 38 preferably has specular reflectivity. Examples of the reflective layer having specular reflectivity include a metal reflective layer made of aluminum, tin, gold, silver, iron, chromium, cobalt, nickel, or alloys thereof, and a nano-laminated film having a metallic luster formed by laminating hundreds to a thousand layers of different types of polymers with a thickness of several nanometers (for example, "PICASUS" manufactured by Toray Co., Ltd.). The metal reflective layer can serve as a conductive reflective layer and have both the reflective layer function and the electrode layer function.
[0183] Regarding the thickness of the reflective layer, in the case of a metal reflective layer, it can be, for example, 0.01µm to 0.10µm, preferably 0.01µm to 0.45µm, and in the case of a nano-laminated film, it can be, for example, 20µm to 300µm, preferably 30µm to 250µm.
[0184] The reflective layer can be formed by a vacuum film-forming method such as vacuum evaporation, sputtering, or ion plating.
[0185] The PDLC film 100d can be obtained, for example, by the following manufacturing method, which comprises the following steps: preparing an unpatterned PDLC film, the unpatterned PDLC film sequentially comprising a second conductive substrate without a reflective layer, an unpatterned PDLC layer, and a second conductive substrate including a reflective layer; irradiating the unpatterned PDLC film with active energy rays from the side of the second conductive substrate without a reflective layer; and providing an ultraviolet blocking layer on the outer side of the second conductive substrate without a reflective layer. The active energy ray irradiation is performed in a state where no voltage is applied between the two substrates or in a state where a voltage is applied between the two substrates.
[0186] Example
[0187] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples. The measuring methods of each characteristic are as follows. In addition, unless otherwise clearly stated, the "parts" and "%" in the examples and comparative examples are weight references.
[0188] (1) Thickness
[0189] The measurement was performed using a digital micrometer (manufactured by Anritsu Corporation, product name “KC-351C”).
[0190] (2) Volume average particle size of liquid crystal particles in liquid crystal emulsion
[0191] 0.1 wt% of liquid crystal emulsion was added to 200 ml of electrolyte aqueous solution (manufactured by COULTER, "Isopar II"), and the resulting mixed solution was used as a measurement sample. Multisizer 3 (manufactured by COULTER, pore size = 20µm) was used to divide the particles from 0.4µm to 12µm into 256 particles at equal intervals on a logarithmic basis, and the volume of each particle size was counted after discretization to calculate the volume average particle size. It should be noted that in the case of particles larger than 12µm, the pore size was set to 30µm, and the particles from 0.6µm to 18µm were divided into 256 particles at equal intervals on a logarithmic basis, and the volume of each particle size was counted after discretization to calculate the volume average particle size.
[0192] (3) Average particle size of resin particles
[0193] A few drops of the resin dispersion were added to 100 mL of water to prepare a measurement sample. A dynamic light scattering particle size distribution measuring device (Microtrac, Inc., device name "Nanotrac 150") was used, the measurement sample was placed in the measuring holder of the device, and the measurement was performed after confirming the measurable concentration using the monitor of the device.
[0194] (4) Haze
[0195] The measurement was performed using "NDH4000" manufactured by Nippon Denshoku Co., Ltd. in accordance with JIS K 7136. For the PDLC film including the ultraviolet blocking layer, the ultraviolet blocking layer was peeled off and then the measurement was performed.
[0196] (5) Absorbance
[0197] The film to be measured was measured using "UH-4150AD+" manufactured by Hitachi High-Tech Science Co., Ltd., using an apparatus equipped with a direct incidence detector.
[0198] [Example 1]
[0199] (Production of conductive substrate)
[0200] An ITO layer was formed on one surface of a PET substrate (manufactured by Toyobo Co., Ltd., product name "COSMOSHINE", thickness: 50µm) by sputtering to obtain a conductive substrate having a structure of [transparent substrate / transparent electrode layer]. The absorbance of the PET substrate at a wavelength of 350nm was 0.15.
[0201] (Preparation of emulsion coating liquid)
[0202] 53.7 parts of a non-polymerizable liquid crystal compound (JNC, product name "LX-153XX", birefringence Δn = 0.149 (ne = 1.651, no = 1.502), viscosity = 48.5 mPa·s), 5.9 parts of a polymerizable liquid crystal compound (Merck, product name "RM257"), 0.1 parts of a photopolymerization initiator (IGM, product name "OMNIRAD184", maximum absorption wavelength 243nm, 331nm), 39.8 parts of pure water, and 0.5 parts of a dispersant (Daiichi Kogyo Seiyaku, "NOIGEN ET159") were mixed and stirred at 100 rpm for 10 minutes using a homogenizer to prepare a liquid crystal emulsion. The average particle size of the liquid crystal particles in the obtained liquid crystal emulsion was 3.4µm.
[0203] 38.4 parts of the above-mentioned liquid crystal emulsion, 19.1 parts of a polyether polyurethane resin aqueous dispersion (manufactured by DSM, trade name "NeoRez R967", polymer average particle size: 80 nm, CV value = 0.27, solid content: 40 wt%), 17.0 parts of a polyester polyurethane resin aqueous dispersion (manufactured by Sanyo Chemical Industry, trade name "U-coat C-102", polymer average particle size: 168 nm, CV value = 0.23, solid content: 45 wt%), 0.1 part of a leveling agent (manufactured by DIC Corporation, product name "F-444"), 1.1 parts of a crosslinking agent (tris[3-(2-methylaziridin-1-yl) propionate] = 1-propylene trimethylolpropionate) and 24.3 parts of pure water were mixed to obtain an emulsion coating liquid (solid content concentration: 40 wt%).
[0204] (Application and drying of emulsion coating liquid)
[0205] The emulsion coating liquid was applied to the ITO layer of the conductive substrate to form a coating layer with a thickness of 20 μm. The coating was performed using a slit die with a line speed of 6 m / min. Then, the coating layer was dried at 25° C. for 8 minutes to form an unpatterned PDLC layer with a thickness of 8 μm.
[0206] (Fabrication of unpatterned PDLC film)
[0207] Using a laminator and applying a lamination pressure of 0.4 MPa / m, another conductive substrate was laminated on the unpatterned PDLC layer such that the ITO layer and the unpatterned PDLC layer faced each other, thereby obtaining an unpatterned PDLC film.
[0208] (Active energy ray irradiation)
[0209] For both sides of the unpatterned PDLC film, a portion of the conductive substrate was half-cut to the transparent substrate to expose the transparent electrode layer, and the exposed portion was used as the extraction electrode. A photomask having a predetermined pattern was placed on the unpatterned PDLC film that had been subjected to electrode treatment, and a UV-LED lamp (manufactured by Hamamatsu Photonics, product name "C11924-101", peak wavelength 365nm) was applied at 10mW / cm 2 The exposure treatment was performed for 10 minutes. Thus, a first region including an aligned liquid crystal polymer and a non-polymerizable liquid crystal compound and a second region including a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound were formed in the PDLC layer, thereby obtaining a patterned PDLC film having a structure of [conductive substrate / patterned PDLC layer / conductive substrate].
[0210] The obtained patterned PDLC film had a haze of 7.8% in the irradiated area and 88.0% in the non-irradiated area when no voltage was applied, and had a haze of 3.7% in the irradiated area and 3.6% in the non-irradiated area when an AC voltage of 50 V was applied.
[0211] (Lamination of UV blocking layers)
[0212] A UV absorbing triacetyl cellulose (TAC) film (Konica Minolta, "KC8UA", thickness 80 μm) as a UV blocking layer was bonded to one conductive substrate side surface of the patterned PDLC via an acrylic adhesive layer. Thus, a patterned PDLC film having a structure of [first conductive substrate (KC8UA / PET substrate / ITO layer) / patterned PDLC layer / second conductive substrate (ITO layer / PET substrate)] was obtained.
[0213] [Example 2]
[0214] A patterned PDLC film having a structure of [first conductive substrate (U4-400CL / PET substrate / ITO layer) / patterned PDLC layer / second conductive substrate (ITO layer / PET substrate)] was obtained in the same manner as in Example 1, except that a UV absorbing film "U4-400CL" (thickness 60 µm) manufactured by Nexfil was bonded as a UV blocking layer.
[0215] [Example 3]
[0216] A patterned PDLC film having a structure of [first conductive substrate (TJ25UL / U4-400CL / PET substrate / ITO layer) / patterned PDLC layer / second conductive substrate (ITO layer / PET substrate)] was obtained in the same manner as in Example 1, except that a UV absorbing film "U4-400CL" and a UV absorbing TAC film (manufactured by FUJIFILM, "TJ25UL", thickness 25µm) were laminated in sequence from the PDLC layer side as ultraviolet blocking layers.
[0217] [Comparative Example 1]
[0218] The patterned PDLC film before the ultraviolet blocking layer was attached was used as the patterned PDLC film of Comparative Example 1.
[0219] <Light resistance evaluation 1>
[0220] The patterned PDLC film of Comparative Example 1 was subjected to a 30°C, 55% RH, 120 W / m2 radiation at one side using a super xenon weathering tester SX-75 (manufactured by Suga Test Instruments Co., Ltd.). 2 (300nm-400nm) xenon light was irradiated for 125 hours, and voltage was applied to the PDLC film after the predetermined irradiation time, and the haze of the non-irradiated area was measured. The measurement results are shown in Fig. 9 .
[0221] <Light resistance evaluation 2>
[0222] The patterned PDLC films of Examples 1 to 3 were subjected to a super xenon weathering tester SX-75 (manufactured by Suga Test Instruments Co., Ltd., under conditions of 30° C. and 55% RH) at 120 W / m 2 The PDLC film was irradiated with xenon light (300nm-400nm) for 125 hours. The haze of the non-irradiated area was measured when a voltage of 0V to 50V was applied to the PDLC film before and after irradiation. The absorption spectrum of the ultraviolet blocking layer using the measurement results is shown together in Fig.10 .
[0223] from Fig. 9 and Fig.10It can be seen that the ultraviolet blocking layer is set on the side of the patterned PDLC film exposed to ultraviolet rays, thereby suppressing the reduction of the haze change in the non-irradiated area. Specifically, the haze of the non-irradiated area of the patterned PDLC film of Example 1 was 3.6% and 86.5% when a 50V voltage was applied and when no voltage was applied before irradiation with xenon light, and the haze when a 50V voltage was applied and when no voltage was applied was 15.0% and 82.0% respectively after irradiation for 125 hours. It should be noted that in the light resistance evaluation of the patterned PDLC film of Comparative Example 1, the haze of the non-irradiated area was 3.6% and 88.0% when a 50V voltage was applied and when no voltage was applied before irradiation with xenon light, and the haze when a 50V voltage was applied and when no voltage was applied was 52.7% and 85.3% respectively after irradiation for 125 hours. It is also found that, for Example 3 having an ultraviolet blocking layer having high absorbance in the entire wavelength range of 300 nm to 380 nm and at a wavelength of 400 nm, the rate of change in haze before and after irradiation with xenon light is 0.3% or less, indicating extremely excellent light resistance.
[0224] Industrial Applicability
[0225] The PDLC film of the present invention can be suitably used in various applications such as displays such as advertisements and billboards, and smartphones.
[0226] Explanation of symbols
[0227] 100 PDLC film
[0228] 10. 1st conductive substrate
[0229] 20 PDLC layer
[0230] 22 Polymer Matrix
[0231] 24 LCD droplets
[0232] 24a Polymerizable liquid crystal compound
[0233] 24b Non-polymerizable liquid crystal compound
[0234] 24c Liquid Crystal Polymer
[0235] 30 Second conductive substrate
Claims
1. A polymer dispersed liquid crystal film, comprising a first conductive substrate, a polymer dispersed liquid crystal layer and a second conductive substrate in sequence, wherein the polymer dispersed liquid crystal layer comprises a polymer matrix and liquid crystal droplets and a photopolymerization initiator dispersed in the polymer matrix, The polymer dispersed liquid crystal layer has a first region and a second region having different haze changes after voltage is applied when viewed from above. The haze change amount after voltage application in the first region is smaller than the haze change amount after voltage application in the second region. The liquid crystal droplets in the second region include a polymerizable liquid crystal compound and a non-polymerizable liquid crystal compound, The liquid crystal droplets in the first region include a liquid crystal polymer which is a polymer of the polymerizable liquid crystal compound and the non-polymerizable liquid crystal compound. The first conductive substrate includes an ultraviolet blocking layer.
2. The polymer dispersed liquid crystal film according to claim 1, wherein: The absorbance of the ultraviolet blocking layer at a wavelength of 350 nm is 2 or more.
3. The polymer dispersed liquid crystal film according to claim 1, wherein: When the maximum absorption wavelength on the longest wavelength side of the photopolymerization initiator is defined as Ann, the absorbance of the ultraviolet blocking layer in the wavelength range of A-30nm to A+50nm is 5 or more.
4. The polymer dispersed liquid crystal film according to claim 1, wherein: When the maximum absorption wavelength on the longest wavelength side of the photopolymerization initiator is defined as Ann, the absorbance of the ultraviolet blocking layer at a wavelength of A+70 nm is 1.8 or more.
5. The polymer dispersed liquid crystal film according to claim 1, wherein: The photopolymerization initiator has a maximum absorption wavelength in the range of 300 nm to 340 nm.
6. The polymer dispersed liquid crystal film according to claim 1, wherein: The second conductive substrate includes an ultraviolet blocking layer or a reflecting layer.
7. The polymer dispersed liquid crystal film according to claim 1, wherein: The weight ratio of the non-polymerizable liquid crystal compound to the polymerizable liquid crystal compound in the second region, ie, the non-polymerizable liquid crystal compound: the polymerizable liquid crystal compound, is 99:1 to 70:
30.
8. The polymer dispersed liquid crystal film according to claim 1, wherein: The difference between the haze of the first region and the haze of the second region increases due to application of voltage.
9. The polymer dispersed liquid crystal film according to claim 1, wherein: The difference between the haze of the first region and the haze of the second region is reduced by application of voltage.
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2